PLACEBO - PLasticizers, Additives, miCroplastics in sEawater in SvalBard ArchipealgO - Giulia Vitale; Massimiliano Vardé; Federico Giglio; Stefano Miserocchi; Sara Giansiracura; Mathia Sabino; Beatrice Rosso; Ingeborg Hallanger; Fabiana Corami (Nessuno, 2023)
Microplastics (MPs; > 100 μm) have been analyzed in several studies while small microplastics (SMPs; < 100 μm), additives, and plasticizers (APs) presence in the water column has not been investigated yet in detail. Svalbard Archipelago is a significant area for the identification of these particles. They can flow into the Arctic waters from mid and low latitudes by ocean currents and winds and they can be more easily transported than larger particles. Also, coastal sources, sea ice, and glaciers melting may locally contribute to their presence in Arctic seawater. Moreover, the evaluation of SMPs and APs' is essential since invertebrates can ingest these particles entering the trophic web and the abundance of these particles is mostly higher than that of components > 100 μm. In September 2022, surface water samples were collected with Niskin Bottles along Kongsfjorden and Krossfjorden. Fieldwork activities were carried out on the MS-Teisten small research vessel. The seawater samples have been partially processed at the Dirigible Italia Arctic station laboratories using filtering apparatus and GF/F filters. Onsite filtration was essential to facilitate the transport of samples back to the laboratories in Venice, where the elutriation procedure will be carried out. Sampling and laboratory activities were conducted by reducing the potential sources of contamination and wearing cotton clothes and nitrile gloves. Field and laboratory blanks were made during each activity. This project aims to (i) give a great field contribution to expand the current knowledge on SMPs (<100 μm), (ii) fill the knowledge gap on APs that provide specific physicochemical properties to polymers, (iii) investigate the different contributions of surface waters, glaciers, and sea ice melt, (iv) and build a broader picture of the potential sources of release, transport, and accumulation of these particles in the marine environment.